Oral and Fecal Microbiome in Molar-Incisor Pattern Periodontitis - Amado, Pâmela Pontes Penas; Kawamoto, Dione; Albuquerque-Souza, Emmanuel; Franco, Diego Castillo; Saraiva, Luciana; Casarin, Renato Corrêa Viana; Horliana, Anna Carolina Ratto Tempestini; Mayer, Marcia Pinto Alves (Frontiers in Cellular and Infection Microbiology, 2020)
In order to improve our understanding on the microbial complexity associated with Grade C/molar-incisor pattern periodontitis (GC/MIP), we surveyed the oral and fecal microbiomes of GC/MIP and compared to non-affected individuals (Control). Seven Afro-descendants with GC/MIP and seven age/race/gender-matched controls were evaluated. Biofilms from supra/subgingival sites (OB) and feces were collected and submitted to 16S rRNA sequencing. Aggregatibacter actinomycetemcomitans (Aa) JP2 clone genotyping and salivary nitrite levels were determined. Supragingival biofilm of GC/MIP presented greater abundance of opportunistic bacteria. Selenomonas was increased in subgingival healthy sites of GC/MIP compared to Control. Synergistetes and Spirochaetae were more abundant whereas Actinobacteria was reduced in OB of GC/MIP compared to controls. Aa abundance was 50 times higher in periodontal sites with PD≥ 4 mm of GC/MIP than in controls. GC/MIP oral microbiome was characterized by a reduction in commensals such as Kingella, Granulicatella, Haemophillus, Bergeyella, and Streptococcus and enrichment in periodontopathogens, especially Aa and sulfate reducing Deltaproteobacteria. The oral microbiome of the Aa JP2-like+ patient was phylogenetically distant from other GC/MIP individuals. GC/MIP presented a higher abundance of sulfidogenic bacteria in the feces, such as Desulfovibrio fairfieldensis, Erysipelothrix tonsillarum and Peptostreptococcus anaerobius than controls. These preliminary data show that the dysbiosis of the microbiome in Afro-descendants with GC/MIP was not restricted to affected sites, but was also observed in supragingival and subgingival healthy sites, as well as in the feces. The understanding on differences of the microbiome between healthy and GC/MIP patients will help in developing strategies to improve and monitor periodontal treatment.